The Predictors of Business Performance Among Culinary MSMEs in West Karawang, West Java Province, Indonesia - Shelinna Shelinna; Kartika Nuringsih (International Journal of Application on Economics and Business, 2023)
Along with the lifestyle of the people who like traditional cuisine, this change is an opportunity for culinary businesses, including the traditional culinary of West Karawang. As an industrial area not far from the city of Jakarta, the development of culinary businesses has an impact on economic growth and the preservation of local wisdom. Therefore, a study was conducted to analyze the determinants of business performance based on market-orientation, entrepreneurial orientation, and entrepreneurial competence. The population is micro, small, and medium enterprises (MSMEs) in the culinary sector in West Karawang with a sampling technique based on purposive sampling with the criteria of Karawang culinary or Sundanese cuisine. The analysis technique uses a quantitative approach with data collection techniques using questionnaires. 113 respondents were filling out the questionnaire. The results of the structural regression test identify that the influence of market orientation and entrepreneurial orientation is not significant, while entrepreneurial competence has a significant effect at the 5% on business performance. The results show third variable has significant positive effect on the business performance of the culinary sector UMKM in West Karawang. Therefore, local government needs to foster local economic growth while preserving traditional Sundanese recipes to maintain the sustainability of culinary treasures in the future.